Implementasi Kebijakan Pencegahan Stunting Di Kelurahan Talise Valangguni Kecamatan Mantikulore Kota Palu - Ananda, Annisa; Daswati; Ferianto, Fiki (Program Studi Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Tadulako, 2024)
This study aims to determine describe, and analyze the implementation of stunting prevention policy in Talise Valangguni sub-district, Mantikulore sub-district using the Merilee S. Grindle policy implementation model consists of aspects of the content of policy and the implementation environment (context of implementation).. The research method used is Descriptive Qualitative, where data is collected through observation, interviews and document studies. This study found that the implementation of the stunting program has not run optimally, the factors that cause it are financial resources that are still not enough to provide all assistance to affected communities. The level of compliance in the community is also a factor that influences stunting cases to continue to increase, there are still many people who do not know what a healthy lifestyle is and proper parenting to healthy feeding. The community also does not utilize the assistance provided properly according to directions from the Health Office and the Government.